2019
DOI: 10.1371/journal.pone.0214362
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of radius or ulna fractures in the elderly: A systematic review covering effectiveness, safety, economic aspects and current practice

Abstract: Background The objective of the present study was to evaluate effectiveness, complications and cost-effectiveness of any surgical or non-surgical treatment for radius or ulna fractures in elderly patients. Secondary objectives were to analyze present treatment traditions of distal radius fractures (DRF) in Sweden and to calculate resource usage for its treatment. Methods and findings The assessment contains a systematic review of clinical and health economic studies com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 80 publications
2
23
0
Order By: Relevance
“…While a majority of all DRFs can be managed non-surgically, about 20% are treated surgically [ 1 , 2 ]. Recent studies have reported that the proportion of surgically managed fractures is increasing, and that the preferred surgical method has shifted from percutaneous techniques to ORIF over the last two decades [ 1 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…While a majority of all DRFs can be managed non-surgically, about 20% are treated surgically [ 1 , 2 ]. Recent studies have reported that the proportion of surgically managed fractures is increasing, and that the preferred surgical method has shifted from percutaneous techniques to ORIF over the last two decades [ 1 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the small advantages in terms of faster recovery should be also weighted in terms of health care costs. For example, Tahir et al reported overall costs of 12 033 USD for the surgical management ( 25 ), while Navarro et al quantified in 137 USD the cost of the conservative cast treatment ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different treatment options have been developed through the years, the most common being non-operative closed reduction and cast immobilization (CR) or operative open reduction and internal fixation (ORIF) with volar locking plate (VLP) ( 10 , 11 ). Each treatment has pros and cons: cast treatment requires longer recovery time and offers a less perfect radiological reduction of the fracture, but it is safer and more economic, on the opposite, ORIF is thought to offer good fracture alignment, faster clinical improvement, and early return to routine activities but at the price of surgical risks such as infection, cut-out, and higher costs ( 12 , 13 , 14 , 15 ). Up to now, there is a lack of evidence and consensus in the literature regarding the best treatment for DRFs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All unit costs are presented in Table 2 . Unit costs for operating theatre including staff were derived from a report by the Swedish Agency for Health Technology Assessment and Assessment of Social Services (SBU) [ 11 ]. Costs regarding in-and outpatient care including emergency ward visits were collected from the diagnose-related group (DRG [ 12 ]) financial reimbursement system used at the hospital.…”
Section: Methodsmentioning
confidence: 99%